A Study of Rapid Leishman Stain on Peripheral Blood Smear - Essgir, Prem Kumar; Anantharamaiah, Hemalatha (Annals of Pathology and Laboratory Medicine, 2019)
Background: Romanowsky stains are universally used for routine staining of peripheral blood smears. Among these Leishman stain is most commonly used in hematology laboratories worldwide. This study was done to stain peripheral blood smears with modified Leishman stain (MLS) on Day 1, Day 5, Day 10 of preparation of the stain and to assess the quality of staining by scoring the stained smears by calculating the Quality Index (QI) and comparing the scores with normal peripheral smear. Methods: Study was done in the hematology section of our institute from December 2016 to February 2017 on a sample size of hundred and one. (MLS) was prepared by adding phenol to the Leishman stain. All cases were stained with modified Leishman stain on day 1, 5 and 10 after preparing the stain. All the smears were scored based on overall staining, cytoplasmic staining, nuclear morphology, red cell staining and platelet staining. Quality index was calculated by dividing the score obtained by maximum score possible. Result: Overall staining, cytoplasmic staining, nuclear morphology, red cell staining and platelet staining were better on day 10 after preparation of MLS when compared to day 1 and day 5. The Quality Index of stained smears normal leishman stained smear was 0.95, score on day 1 of preparing stain was 0.71, score on day 5 was 0.73 and day 10 of preparing stain was 0.89. Conclusion: MLS can be used for staining of thin peripheral blood smears in 4 minutes, unlike the conventional Leishman stain method which takes about 10-15 minutes.